2003
DOI: 10.1099/vir.0.19323-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular comparison of isolates of an emerging fish pathogen, koi herpesvirus, and the effect of water temperature on mortality of experimentally infected koi

Abstract: Koi herpesvirus (KHV) has been associated with devastating losses of common carp (Cyprinus carpio carpio) and koi (Cyprinus carpio koi ) in North America, Europe, Israel and Asia. A comparison of virion polypeptides and genomic restriction fragments of seven geographically diverse isolates of KHV indicated that with one exception they represented a homogeneous group. A principal environmental factor influencing the onset and severity of disease is water temperature. Optimal growth of KHV in a koi fin cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
170
1
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(199 citation statements)
references
References 25 publications
15
170
1
9
Order By: Relevance
“…CyHV-3 displays optimal growth at 15-25 1C in vitro, whereas growth is very low at o10 1C and undetectable at 430 1C (Gilad et al, 2003). As expected from the temperature dependence, CyHV-3 increased in host tissues in the spring after the water temperature exceeded 15 1C (Figure 4a).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…CyHV-3 displays optimal growth at 15-25 1C in vitro, whereas growth is very low at o10 1C and undetectable at 430 1C (Gilad et al, 2003). As expected from the temperature dependence, CyHV-3 increased in host tissues in the spring after the water temperature exceeded 15 1C (Figure 4a).…”
Section: Discussionsupporting
confidence: 53%
“…However, an increasing number of experimental studies have investigated fluctuations of CyHV-3 in hosts and its possible transmission routes. In vitro experiments with carp cell lines have demonstrated that CyHV-3 growth depends on host cell temperature; optimal growth occurs at 15-25 1C, whereas temperatures lower than 10 1C or higher than 30 1C result in very low or undetectable virus replication (Gilad et al, 2003). Such temperature dependence also occurs in another viral pathogen of common carp, the spring viremia of the carp virus (Ahne et al, 2002).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other common fish cell lines such as FHM, RTG-2, CHSE-214 and EPC do not support the growth of KHV [14,60,65]. The optimal temperature for viral propagation in KF-1 cells is 15-25°C; at 30°C these cells do not produce virus [26]. The virus induces typical plaques in 3-4 days after inoculation in the cultured cells along with the formation of syncytia and increase in cytoplasmic vacuoles.…”
Section: Viral Propagationmentioning
confidence: 95%
“…Massive mortalities occur within a week of onset of clinical signs, with the mortality rate reaching 80-100 % [84]. At temperatures above 30°C or below 13°C, KHV becomes dormant and clinical signs generally cease [12,26]. Viral DNA can be detected in the blood and kidney, 1 day after virus exposure [17,65].…”
Section: Transmissionmentioning
confidence: 99%